STRATEGI GURU DALAM MANAJEMEN KELAS PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI SDN PEJUANG 7 - Pradevi, Yuliana Elsa; Muhammad Rijal Fadli; Nurul Febrianti; Khusnul Fatonah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem of ineffective classroom management in Pancasila Education learning in class III D of SDN Pejuang 7, characterized by a monotonous and teacher-centered approach resulting in a less conducive classroom atmosphere and less active student involvement. The purpose of the study is to analyze teacher strategies in classroom management through three sub-focuses: student arrangement, discipline management, and the creation of a learning atmosphere on the topic "Different is Beautiful". The study used a descriptive qualitative method with subjects of class III D teacher and five students selected purposively. Data collection was carried out through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that teachers implemented three dimensions of integrated strategies: (1) student arrangement through a daily seating rotation system and the formation of heterogeneous study groups; (2) discipline management through the establishment of clear class rules and a positive discipline approach based on conflict mediation; and (3) the creation of a learning atmosphere through ice breaking, a variety of learning methods, and a consistent reward system. The implementation of these three strategies successfully strengthened the values of tolerance and respect for diversity in students.